2021
DOI: 10.3390/su13137353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential Role of Bacillus altitudinis MT422188 in Nickel Bioremediation from Contaminated Industrial Effluents

Abstract: The incessant pervasiveness of heavy metals in the environment is one of the precursory factors of pollution. This research study was endeavored upon to investigate the bioremediation potential of a nickel (Ni)-resistant bacterial isolate, identified as Bacillus altitudinis MT422188, whose optimum growth parameters were demonstrated at pH 7, temperature 32 °C, and 1 mM phosphate. Minimal Inhibitory Concentration (MIC) and EC50 for Ni were observed to be 20 and 11.5 mM, respectively, whereas the cross heavy-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…To date, several papers on biosorption with Bacillus spp. have been published [ 21 , 60 , 61 , 62 ]. Some strains of the Bacillus spp.…”
Section: Heavy Metal Bioremediation Strategies Detected In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several papers on biosorption with Bacillus spp. have been published [ 21 , 60 , 61 , 62 ]. Some strains of the Bacillus spp.…”
Section: Heavy Metal Bioremediation Strategies Detected In ...mentioning
confidence: 99%
“…One way of bioremediation may be the use of bacteria of the genus Bacillus [ 8 , 17 , 18 , 19 , 20 , 21 ]. They are Gram-positive, spore-forming, rod-shaped, and aerobic or facultative anaerobes.…”
Section: Introductionmentioning
confidence: 99%
“…B. altitudinis has been isolated from various environments, including thermal pools (Abdollahi et al, 2021). Likewise, this species has been associated with good capacities to tolerate heavy metals, as well as excellent capacities to bioremediate environments contaminated with zinc, nickel, and copper (Khan et al, 2021; Babar et al, 2021; Yue et al, 2021). On the other hand, B. paralicheniformis KNPhave shown a good capacity to reduce chromate through three possible chromate efflux transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic thermophilic bacterium Anoxybacillus was reported to be chemotactic towards Fe (III) and showed over 50% reduction of Fe (III) in studies with co-contamination with hydrocarbons [96]. In another study, Bacillus altitudinis MT422188 was found to be chemotactic towards zinc [97] and nickel [98] which aided in efficient biosorption of these heavy metals.…”
Section: ) Heavy Metalsmentioning
confidence: 99%